Paradoxical support: exploring use of the holistic needs assessment and its contribution to meaningful support for women with breast cancer - Briggs, Lydia (2021)
Breast cancer is a widespread disease, with rapidly increasing numbers of people living with or beyond this diagnosis (Breast Cancer Care, 2018a). The disease is associated with a complex array of physical, psychological and social impacts, which may continue long after treatment (National Cancer Institute, 2014). The concept of ‘personalised care’ (formerly the ‘recovery package’) was introduced in the UK as part of a nation-wide agenda to support women with breast cancer, of which holistic needs assessment (HNA) is a core element (National Health Service (NHS), 2019). These assessments give people opportunities to raise their concerns and have these addressed through a meaningful discussion and subsequent care plan (National Cancer Survivorship Initiative, 2013). Across the UK, implementation of the HNA varies significantly in its approach and delivery methods. Although various types of HNA tools exist, few studies have explored the perspective of either healthcare professionals or individuals with cancer around use of these tools. However, there is some indication that the HNA’s contribution to addressing concerns arising from cancer diagnoses is complex, and often minimal.